HAK DAN KEWAJIBAN PEMILIK BANGUNAN CAGAR BUDAYA DI KOTA MALANG - Susanti, Diah Imaningrum; Susriyani, Rini; Herwanta, Albertus (Penerbit Universitas Atma Jaya Yogyakarta, 2020)
The objectives of this research are to describe the implementation of the rights and duties of the owners of cultural properties (Cagar Budaya) in Malang City, especially the buildings of Cor Jesu School and Kayutangan Church, as well as to describe the responsibilities of the local government in protecting the buildings stipulated as cultural properties as stated in the Law NumberÂ 11 of 2010 on Cultural Properties. The status as â€œcultural propertyâ€ is stipulated by local government through a recommendation by a Team of Experts in Cultural Property. After the stipulation, the rights and liabilities of the owner of such cultural property take effect and the protection of the property becomes the responsibility of the local government. The approach of this research is empirical, conducted by doing in-depth interviews with the owners of cultural properties, some informants such as the Cultural and Tourism Department of Malang City, and with the Assessor of Cultural Property for those buildings. This approach is done after identifying the rights, duties, and responsibilities dealing with the cultural proprties as stipulated in the Law Number 11 of 2010 on Cultural Property. It is concluded that the law as it is written in the Law still takes great efforts to be implemented in reality, in order to fulfill the requirements stated in the Law.Â